Effect of Mirror Therapy Technique and Physical Therapy Exercise on Motor Function for upper and lower extremity among Patients with Stroke (comparative study) - محمود يوشع; فاطمة قريط; أكثم هيفا (Latakia University Journal -Medical Sciences Series, 2024)
The mirror therapy technique and physical therapy exercises are considered important interventions that have a positive effect on the motor function of stroke patients in the chronic stage. Therefore, the current study aimed to evaluate the effect of the mirror therapy technique and physical therapy exercises on 45 chronic stroke patients who were selected using a convenience sampling method. From the Department of Physical Therapy at Tishreen University Hospital in Lattakia, data was collected using the fugel-Meyer assessment. The results showed a significant improvement in motor function for the mirror therapy group compared to other treatments. The study recommended applying mirror therapy as an alternative or complementary intervention with other treatments and conducting more research on the effect of mirror therapy on other disabilities non-kinetics and the potential risks of its application.